2013
DOI: 10.5423/ppj.si.07.2012.0117
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Systemic Resistance against Cucumber mosaic virus in Arabidopsis thaliana by Trichoderma asperellum SKT-1

Abstract: Trichoderma asperellum SKT-1 is a microbial pesticide that is very effective against various diseases. Our study was undertaken to evaluate T. asperellum SKT-1 for induction of resistance against yellow strain of Cucumber mosaic virus (CMV-Y) in Arabidopsis plants. Disease severity was rated at 2 weeks post inoculation (WPI). CMV titre in Arabidopsis leaves was determined by indirect enzyme-linked immunosorbent assay (ELISA) at 2 WPI. Our results demonstrated that among all Arabidopsis plants treated with barl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 52 publications
4
58
0
1
Order By: Relevance
“…In the second trial, the differences between the variants were more clear and in accordance with the previous studies (Elsharkawy et al, 2013). The second set of experiments was original by studying rockwool as a substrate, compared with the results on the conventional soil cultivation.…”
Section: Second Inoculation: Direct Root Inoculationsupporting
confidence: 69%
“…In the second trial, the differences between the variants were more clear and in accordance with the previous studies (Elsharkawy et al, 2013). The second set of experiments was original by studying rockwool as a substrate, compared with the results on the conventional soil cultivation.…”
Section: Second Inoculation: Direct Root Inoculationsupporting
confidence: 69%
“…The ability of Trichoderma spp. to induce systemic resistance in dicotyledonous and monocotyledonous plants has been demonstrated against different pathogens, including the fungus S. sclerotiorum in tomato and cauliflower [18], the bacteria Ralstonia solanacearum in tomato [19], the cucumber mosaic virus in A. thaliana [20], and the nematode Meloidogyne incognita in Vigna radiate [21]. The fungus T. viride can induce systemic resistance against Fusarium oxysporum and Alternaria spp.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, an increment in the defenserelated enzymes, that are, POX and PPO and total protein contents was observed in rice cultivars as a result of inoculation with T. barclayana. Among induced defense responses, production and accumulation of pathogensis related proteins are very important (Van Loon et al, 2006;Elsharkawy et al, 2012a, b;Elsharkawy et al, 2013;Hassan et al, 2014). Attempts have been made to exploit these anti-fungal proteins to develop disease resistant transgenic crop plants (Lin et al, 1995;Tabei et al, 1997).…”
Section: Relationship Between the Tested Rice Cultivars And Isolates mentioning
confidence: 99%
“…It was reported that plants defend themselves from the invader pathogens by either their structural barriers or antimicrobial compound which prevent colonization of the tissues. The induced defense responses include hypersensitive responses, the production of reactive oxygen species (ROS), pathogensis-related protein and ion fluxes across the plasma membrane (Zhao et al, 2005;Elsharkawy et al, 2012a, b;Elsharkawy et al, 2013;Hassan et al, 2014).…”
mentioning
confidence: 99%